DECISIONS OF THE GRAND NATIONAL ASSEMBLY FROM THE PERSPECTIVE OF THE CONTEMPORARY INTERNATIONAL LAW ON PEOPLE’S SELF DETERMINATION - Vučić, Mihajlo (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Right to self-determination has in the last hundred years been developed through a string of international legal acts and a string of different contexts of international relations. This fact has influenced its contemporary normative content which is not stripped of political dimension. The author identifies in the article four criteria which are the key to full enjoyment of contemporary right of self-determination. These are: permanent and heavy breaches of rights of the people who requests self-determination from the state authorities, weak central government in the territory where this people lives, creation of people’s own authorities who can effectively control this territory, support of great powers. Author analyzes the case of self-determination of peoples in Vojvodina to incorporate themselves into Kingdom of Serbia through the prism of these criteria and concludes that from the point of view of contemporary international law this incorporation would be perfectly legal. Key words: self-determination, Vojvodina, international law, great powers